Socialisation of the modern youth in the context of the online resources use - Semak, Vadzim I. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article outlined the problem, associated with the use of the Internet technologies by modern youth in the process of socialisation. The analysis of the results of scientific activity in this direction is made. The separate positive and negative aspects of the using online resources are shown. Attention is focused on the ambivalence of the scientific data and the disadvantage of the scientific information. The general aspects of the concepts of network individualism and network society, the theory of cybersocialisation are outlined.
Keywords: Internet; online resources; social networks; modern youth; socialisation; communications; consciousness; influence